2019
DOI: 10.1371/journal.ppat.1007571
|View full text |Cite
|
Sign up to set email alerts
|

PolyGlcNAc-containing exopolymers enable surface penetration by non-motile Enterococcus faecalis

Abstract: Bacterial pathogens have evolved strategies that enable them to invade tissues and spread within the host. Enterococcus faecalis is a leading cause of local and disseminated multidrug-resistant hospital infections, but the molecular mechanisms used by this non-motile bacterium to penetrate surfaces and translocate through tissues remain largely unexplored. Here we present experimental evidence indicating that E . faecalis generates exopolysac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(66 citation statements)
references
References 96 publications
(127 reference statements)
1
64
0
Order By: Relevance
“…Chatterjee and collaborators recently demonstrated that mutations in genes involved in decorating EPA reduced E. faecalis resistance to antibiotics, but conferred elevated resistance to phage infections in both cultures and in an intestinal colonization mouse model [25]. Our work demonstrated that the absence of either a polyGlcNAc decoration of EPA or a new polyGlcNAc-containing polysaccharide impaired the ability of E. faecalis to move into surfaces, suggesting a new role for these exopolysaccharides [8].…”
mentioning
confidence: 53%
See 4 more Smart Citations
“…Chatterjee and collaborators recently demonstrated that mutations in genes involved in decorating EPA reduced E. faecalis resistance to antibiotics, but conferred elevated resistance to phage infections in both cultures and in an intestinal colonization mouse model [25]. Our work demonstrated that the absence of either a polyGlcNAc decoration of EPA or a new polyGlcNAc-containing polysaccharide impaired the ability of E. faecalis to move into surfaces, suggesting a new role for these exopolysaccharides [8].…”
mentioning
confidence: 53%
“…Indeed, we demonstrated that the RpiA-GlnA-EpaX metabolic axis was also necessary for movement through human intestinal barriers, and this process involved the formation of bacterial aggregates. Thus, strains devoid of either GlnA, RpiA or EpaX had impaired ability to translocate through epithelial cell monolayers [8]. Altogether these results revealed a new role for polyGlcNAc-containing extracellular polysaccharides as key mediators of E. faecalis migration traits.…”
mentioning
confidence: 81%
See 3 more Smart Citations